The effectiveness of the 'matahari' method in improving basic arithmetic skills of junior high school students - Sutarman Borean; Sinambela, Mindo Hotmaida; Marlince Anggelina Siep; Risnauli Y. Nainggolan; Tresya Palungan (Universitas Papua, 2025)
The persistent disparity in students’ mastery of basic arithmetic concepts presents a critical challenge in mathematics education, particularly in regions with limited pedagogical resources. While traditional approaches often fall short in addressing foundational numerical skills, there is a lack of practical, culturally adaptable methods tailored to early secondary learners. This study introduces the